Recognition of Warping Face Image and Morphing Face Image of Two Warping Image Using Hidden Markov Model (المجلة العراقية للعلوم الاحصائية, 2011)
In this paper, using algorithm models of Hidden Markov models, it has been concluded that the possibility of recognizing the warp face and the morph face the image real departments face on recognizing object. In through applicability Algorithms model of Hidden Markov and allegation with Algorithm (Beier-Neely) get through in to practicability the defining recognizing the warp face image and the morph face image. The results of hidden Markov models indicate that the matrix at the final iterate able to recognize the warp face and the morph face. Programmers of all algorithm are writhen using the language Matlab (R2008a) 7.6.0.